Acute small fiber neuropathy after Oxford‐AstraZeneca ChAdOx1‐S vaccination: A report of three cases and review of the literature. Issue 4 (29th August 2022) - Abbott, Molly G.; Allawi, Zahra; Hofer, Monika; Ansorge, Olaf; Brady, Stefen; Fadic, Ricardo; Torres, Gustavo; Knight, Ravi; Calvo, Margarita; Bennett, David L. H.; Themistocleous, Andreas C.
Abstract: Small fiber neuropathy usually presents with gradual and progressive chronic length‐dependent pain. Acute small fiber neuropathy is rarely reported. Three patients with acute onset neuropathic pain after Oxford‐AstraZeneca ChAdOx1‐S vaccination are described. Two patients were identified at the Oxford University NHS Foundation Trust, Oxford, UK and one patient in Red de Salud UC Christus, Santiago, Chile. All patients underwent a clinical assessment that included a detailed neurological examination, laboratory investigations, nerve conduction studies, thermal threshold testing, and skin biopsy for intra‐epidermal nerve fiber density. Patients seen in Oxford underwent MRI of the brain and spinal cord. Cerebrospinal analysis was not performed. Neuropathic symptoms (burning pain, dysaesthesias) developed in the hands and feet within 2 weeks of vaccination. On clinical examination, there was pinprick and thermal hyposensitivity in the area of neuropathic pain. Laboratory investigation, nerve conduction tests, sympathetic skin responses, and MRI showed no relevant abnormalities. Thermal thresholds were abnormal and intra‐epidermal nerve fiber density in the lower leg was reduced. In two cases symptoms persist after several months. Three cases of definite acute small fiber neuropathy after Oxford‐AstraZeneca ChAdOx1‐S vaccination are described. At follow up, neuropathic pain was present in two of the patients.